Ship disaster threatened environmental security and dwindled down the spirit of maritime Sri Lanka - Sivaramanan, Sivakumaran; Kotagama, Sarath W (Bangladesh Journal of Scientific and Industrial Research, 2022)
The MV Xpress-Pearl ship disaster was a maritime environmental security threat that occurred on the Southwest coast of Sri Lanka during this decade. The wreck consists of tonnes of nitric acid, several other chemicals, and oils such as tonnes of bunker fuel oil, gas oil, and tanks full of lubricating oil. Also, several containers occupied with plastic nurdles that escaped have affected the west and southern coastal belt of Sri Lanka. Carcasses of dead endangered turtles, dolphins and various other rare marine organisms washed ashore, such as beaches of Uswetakeiyawa, Panadura, Unawatuna, Wellawatte, Moratuwa, and Induruwa. Besides, experts believe that it may take a long term to completely recover from the impacts including safe plastic nurdle-free seafood. Green peace USA has purported a list of conditions to be updated, such as the implementation of the plastic pallet free water act and placing plastics into the hazardous material category. The study used the qualitative content analysis technique to reconcile plastic pollution caused by the disaster as an environmental problem. Since plastic pollution is also a repercussion of two known keystone environmental problems, such as urbanization and human population increase. Bangladesh J. Sci. Ind. Res. 57(4), 199-206, 2022